Food consumption in China the revolution continues - Zhou, Zhang-Yue.; Liu, Hongbo; Cao, Lijuan; Edward Elgar Publishing (Cheltenham, U.K. : Edward Elgar Pub. Ltd., 2014)
'This work is not an easy read, for all the right reasons. The authors stay well away from stylised facts, instead providing a rigorous assessment that gives readers a more informed and textured understanding of key drivers of China's food consumption. Beyond academics, commercial firms and prospective trading partners will find this book an important resource; its judicious use of tables, charts, maps and applied work paint a nuanced picture of China's markets' prospects and the challenges that still remain.' --Brad Gilmour, Agriculture and Agri-Food Canada. 'China's food consumption will have a fundamental impact on Chinese and global food supply and demand, and therefore food and nutrition security in the world. In addition, Chinese consumption patterns have important implications on global natural resources and the environment. To design policies and strategies to guide Chinese consumers towards a more sustainable and healthy diet requires solid data and analysis of future Chinese consumption trends. This book is a welcome first step. The authors of this book are some of the most experienced and respected researchers on Chinese agriculture and food issues. It is a valuable source of reference for researchers, government policymakers and anyone in the private sector who is interested in Chinese and global food systems.' --Shenggen Fan, International Food Policy Research Institute, US. 'With the world's largest population and second largest economy, China plays an important role in global food production and consumption. This book by a distinguished group of authors presents an updated analysis of food consumption in China. The material covered is informative and comprehensive. All food-related traders, researchers and analysts would benefit from reading this book.' --Yanrui Wu, The University of Western Australia, Australia. Recent decades have seen China's domestic consumption in sectors such as food, housing, health care, education and travel greatly increase. This important book assesses China's current food consumption trends and the outlook for its future needs of such a crucial commodity. Key features of the book include: A systematic examination of the key elements shaping food consumption, with particular attention to factors peculiar to China; An evaluation of changes in food consumption between rural and urban residents, the rich and poor, and consumers of different regions and identification of the key drivers behind such changes; A comprehensive coverage of all major food items including foodgrains, meats and other animal products, fruits and vegetables, alcoholic drinks, and aquacultural products; and A projection for China's food import needs by 2020. This book will be of great relevance to anyone who is interested in the dynamics of Chinese food consumption, such as commodity traders, leaders of agri-food industries, food trade officials, and food market researchers. It will also prove a valuable reference for undergraduate and postgraduate students majoring in food marketing and trade, general food and agricultural economics and scholars studying food consumption issues.
1. Introduction -- 2. Past studies on China's food consumption -- 3. Recent trends in China's food consumption -- 4. Food consumption dynamics : key drivers and future trends -- 5. Outlook for China's food consumption and import needs -- 6. Further discussion -- 7. Conclusions and implications.
Includes bibliographical references and index.
Keywords: Food consumption -- China; Electronic books